LITERASI KOMUNIKASI KESEHATAN UNTUK GENERASI MUDA DI PANTI YAUMA (ASRAMA YATIM DAN DHU’AFA KEMAYORAN) - Sari, Wulan Purnama; Helen, Helen; Tindaon, Elisabeth Indira Dameria; Khairunnisa, Julia; Michelle, Laurencia; Amesz, Mutiara Fransisca (Jurnal Bakti Masyarakat Indonesia, 2023)
Health communication is the process of conveying health information to encourage change for individuals and groups to improve public health. Health communication is useful for providing information about the importance of maintaining a healthy body and the environment. The issue of health itself is still a problem in Indonesia, plus recently the issue of health has emerged again with the problem of air pollution in Jakarta. Awareness about health is still very minimal for the younger generation, especially for children in orphanages. Therefore, this Community Service Activity (PKM) was carried out at the Yauma Home Kemayoran Orphanage and Dhu'Afa Dormitory to build and increase the knowledge of the younger generation, especially orphanage children, regarding the importance of maintaining a healthy body and the environment. To help solve problems related to health issues, it must start from the younger generation, who are the nation's next generation. The target of this PKM activity is to increase awareness of the younger generation and orphanage children regarding maintaining a clean environment and taking care of their bodies. PKM activities are carried out using the story telling method which is a program in health communication. The results of PKM activities show that after conducting socialization regarding maintaining cleanliness, children in institutions have more awareness about the health of their bodies and the environment around them. The health communication carried out has been proven to bring changes in the knowledge, attitudes and behavior of the younger generation, especially children, in responding to the problem of maintaining body and environmental health ABSTRAK Komunikasi kesehatan merupakan proses penyampaian informasi kesehatan untuk mendorong perubahan bagi individu maupun kelompok untuk meningkatkan kesehatan masyarakat. Komunikasi kesehatan berguna untuk memberikan informasi mengenai pentingnya menjaga kesehatan tubuh dan lingkungan. Isu mengenai Kesehatan sendiri masih menjadi permasalahan di Indonesia, ditambah belakangan terakhir ini isu kesehatan kembali mencuat dengan adanya permasalahan polusi udara di Jakarta. Kesadaran mengenai kesehatan masih sangat minim bagi generasi muda, khususnya bagi anak-anak panti asuhan. Untuk membantu menyelesaikan permasalahan terkait dengan isu kesehatan harus dimulai dari generasi muda, yang merupakan generasi penerus bangsa. Oleh karena itu, Kegiatan Pengabdian Kepada Masyarakat (PKM) ini dilakukan di Panti Yauma Kemayoran Asrama Yatim dan Dhu’Afa untuk membangun dan menambah pengetahuan generasi muda terlebih anak panti mengenai pentingnya menjaga kesehatan tubuh dan lingkungan. Target dari adanya kegiatan PKM ini adalah untuk meningkatkan kesadaran generasi muda, anak-anak panti mengenai menjaga kebersihan lingkungan dan menjaga tubuh. Kegiatan PKM dilakukan dengan menggunakan metode story telling yang menjadi program dalam komunikasi kesehatan. Hasil kegiatan PKM menunjukkan bahwa setelah dilakukannya sosialisasi mengenai menjaga kebersihan, anak-anak di panti lebih memiliki kesadaran mengenai kesehatan tubuh mereka serta lingkungan sekitar mereka. Komunikasi kesehatan yang dilakukan terbukti memberikan pengetahuan, sikap dan perilaku generasi muda terlebih anak-anak dalam menanggapi masalah menjaga kesehatan tubuh dan lingkungan